Development of a simplified commercial-scale aquaponic facility for implementation in northern Uganda - Wicoff, Emily (Kansas State University, 2011)
Current aquaponic technology ranges from backyard hobbyist to technologically advanced commercial production. A single source for protein (fish) and nutrients/vitamins (vegetables), development of a technologically simplified commercial-scale system is a realistic solution for many impoverished nations. This study develops a simplified aquaponic facility to be implemented in rural northern Uganda. Research objectives were to: (1) identify simplified commercial-scale system design components, (2) establish a water quality baseline, (3) identify plant/tilapia production ratios, (4) identify construction materials available in northern Uganda, (5) integrate culturally familiar elements, (6) complete preliminary facility design, and (7) calculate facility water balance. The study established that a viable simplified design achieves: (1) water circulation with weir gravity flow and one return pump, (2) tank cleaning with strategically sloped floors and manual waste siphoning, and (3) breeding control with raised bottom fishnets. Submerged aeration is critical to optimal fish growth, and cannot be eliminated despite surface aeration’s low energy appeal. Baseline water quality parameter values of DO > 3 mg/L, pH > 5.5, and TAN > 3 mg/L (2 mg/L average) were established for the pilot study configuration and hydraulic retention time (HRT). A plant/tilapia ratio of 2.5 ft[superscript]2/lb was identified for the proposed facility’s design. The simplified design was assessed compatible with concrete block construction local to northern Uganda. Incorporating the following culturally familiar elements will facilitate technology adoption: utilize native fish (tilapia) and vegetable crops identified in community markets, replace commercially produced plant tank raft components with woven matting from locally available natural materials, and identify the unfamiliar proposed tank design with newly adopted raceway culture techniques at a well-known Ugandan national fishery institute. A proposed facility preliminary design represents local materials, identified plant/tilapia ratio, minimum HRT, and simplified design components for tilapia densities ranging from 12 to 3 gal/lb. With the facility supplied by both rainwater and groundwater, corresponding water balances for 12 to 3 gal/lb densities ranged from a 9,735 gal/yr well supply demand to a 10,984 gal/yr rainwater surplus.
Keywords: Aquaponics; Tilapia; Uganda; Agriculture, General (0473); Environmental Engineering (0775); Sustainability (0640)